Wakaf Produktif Sumber Mata Air Sebagai Upaya Mewujudkan Kesejahteraan Umat Berdasarkan Undang-Undang Nomor 41 Tahun 2004 Tentang Wakaf - Dodi Mustajab (Universitas Muhammadiyah Purwokerto, 2022)
Society in general considers waqf limited to immovable objects that are used for the common good. For example, land used to build mosques, Islamic boarding schools, schools, cemeteries, and so on. In fact, apart from having a religious spiritual dimension, waqf is actually an Islamic teaching that is beneficial for the welfare of the people. This study aims to describe the waqf of springs as an effort to realize the welfare of the people. This study used qualitative research methods. The data is sourced from primary and secondary data which is processed and analyzed in a descriptive-analytical manner. The results of the study show that water sources can also be used as legal waqf objects. However, it should be underlined that the waqf is a source of water or wells, and not the water itself. This is because water is classified as something that can be consumed / utilized so that it cannot be used as a waqf object. In contrast to wells or water sources that can always flow and provide benefits. In a sense, this water waqf is used for public and religious purposes, such as bathing, drinking, and ablution.Keywords: waqf, water sources, welfare, people.